2019
DOI: 10.3390/ijms20163994
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Expression of Anticoagulation Factor Antistasin in Freshwater Leeches

Abstract: Antistasin, which was originally discovered in the salivary glands of the Mexican leech Haementeria officinalis, was newly isolated from Helobdella austinensis. To confirm the temporal expression of antistasin during embryogenesis, we carried out semi-quantitative RT-PCR. Hau-antistasin1 was uniquely expressed at stage 4 of the cleavage and was strongly expressed in the late stages of organogenesis, as were other antistasin members. In order to confirm the spatial expression of antistasin, we performed fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The salivary glands of leeches contain many anticoagulant and antiplatelet components, such as Theromin, a thrombin inhibitor from leech Theromyzon tessulatum [ 33 ]; Antistasin, a factor Xa inhibitor from the leech Haementeria officinalis [ 35 ]; Ornatins, a GPIIb-IIIa antagonist and platelet aggregation inhibitor from the leech Placobdella ornata [ 40 ]. FXIa inhibitory peptide from leeches has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salivary glands of leeches contain many anticoagulant and antiplatelet components, such as Theromin, a thrombin inhibitor from leech Theromyzon tessulatum [ 33 ]; Antistasin, a factor Xa inhibitor from the leech Haementeria officinalis [ 35 ]; Ornatins, a GPIIb-IIIa antagonist and platelet aggregation inhibitor from the leech Placobdella ornata [ 40 ]. FXIa inhibitory peptide from leeches has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…One is anticoagulant proteins, including thrombin inhibitors and FXa inhibitors; the other is anti-platelet aggregation proteins. The thrombin inhibitors include Hirudin [ 31 ], Haemadin [ 32 ] and Theromin [ 33 ], FXa inhibitors include Therostasin [ 34 ], Antistasin [ 35 ] and Lefaxin [ 36 ], and anti-platelet aggregation proteins include Calin, LAPP (Leech anti-platelet protein), Decorsin and Ornatin [ 37 , 38 , 39 , 40 ]. However, inhibitors targeting FXI from leeches have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…2015 ). Their function is still largely unknown but it has been suggested that they might be related to physiological processes other than antihemostasis ( Kwak et al. 2019 ), such as immune response ( Nikapitiya et al.…”
Section: Discussionmentioning
confidence: 99%
“…2006 ). Moreover, a recent study has suggested that proteins with antistasin-like domains might be involved in segment polarity signaling ( Kwak et al. 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The embryos were washed five times for 3 × 5 min each in PBT at room temperature and heated for 10 min at 80 • C in PBT to inactivate endogenous alkaline phosphatases. Further protocol conditions were identical to those described by Cho et al [33], and double fluorescent in situ hybridization (FISH) was described by Kwak et al [34].…”
Section: Ish In U Unicinctusmentioning
confidence: 99%